ANALISIS NILAI-NILAI SOSIAL TOKOH PADA NOVEL RINTIHAN DARI LEMBAH LIBANON KARYA TAUFIQURRAHMAN AL-AZIZY - Erlina Erlina (Ensiklopedia of Journal, 2020)
This research is motivated by the analysis of social values in Rintihan dari Lembah Libanon novel by Taufiqurrahman Al-Azizy. Social values are a reference, benchmark against the actions or behavior that is raised by the community as a whole. Social values are one of attitude towards an object either it is true or false, good or bad, for public interest in human life. This attitude can be seen in competition, contradiction, disputes or conflicts. This study aimed to describe the form of social values of the characters in Rintihan dari Lembah Libanon novel by Taufiqurrahman Al-Azizy. The research is a qualitative study using descriptive methods. The data in this study is the quotation of social values such as competition, contradiction, disputes or conflicts in Rintihan dari Lembah Libanon novel by Taufiqurrahman Al-Azizy. Based on the opinion above, the source of the data in this study is Rintihan dari Lembah Libanon novel by Taufiqurrahman Al-Azizy. Data collection techniques in this study are: (1) read Rintihan dari Lembah Libanon novel by Taufiqurrahman Al-Azizy to get the data, and (2) marking or record every word, sentence, statement or dialogue related to the research objectives. While the steps in analyzing data are: (1) read and understand the data in the overall data that has been collected, (2) move the data that have been classified into a format 1, (3) classify the data according to the type of social values such as competition, contradiction, disputes or conflicts, and (4) make conclusions and suggestions. The results of this study showed that this novel contains social values that can be seen from the social processes such as competition, contradiction, disputes or conflicts.